A complication following ACL reconstruction using bioabsorbable cross-pins - Vecchini, Eugenio; Micheloni, Gian Mario; Corbo, Valentina Rita; Perusi, Francesco; Dib, Giovanni; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
This is a case of a proximal pin migration after ACL reconstruction in medial soft tissue with pain, inflammatory reaction and functional reduction. 33-year-old male presented at our clinic with a complete ACL rupture. Reconstruction with autogenous gracilis and semitendinosus hamstring tendons was performed and graft fixed in the femoral canal with two PLLA bioabsorbable pins (RIGIDFIX® Cross Pin System). Two months postoperatively the patient presented swelling and pain on the medial side of the knee, full range of motion and negative results at the Lachman and Pivot shift tests. MRI examination showed the superior femoral tunnel crossing both the lateral and medial cortex lodging the pin in the knee’s medial soft tissue corresponding to the swelling area reported by the patient. The tendon graft was properly positioned. After surgical removal of the pin through a small skin incision, the pain and swelling promptly subsided allowing the patient return to normal activities in few weeks without any pain. In our opinion the painful swelling of the knee was due to a displacement of the pin that had been accidentally lodged in the soft tissues instead of the bone causing a foreign-body reaction resulting in granuloma formation with local inflammation. This dislodgement could have been due to an inappropriately long femoral tunnel.